Propuesta de un manual de procedimientos para los departamentos de proveeduría, recursos humanos, enlace comunal, unidad técnica de gestión vial municipal, relleno sanitario y servicios generales de la Municipalidad de San Carlos - Mora-Rodríguez, Melissa (Instituto Tecnológico de Costa Rica, 2014)
This document is a study prepared for the City Hall of San Carlos, that aims at contributing with the administrative management of the institution, through the documentation of procedures for the departments of Human Resources, Community Liaison, General Services, Technical Unit of Municipal Road Management and Provisioning Office, detailing the steps to be undertaken for the development of each of these departments’ activities. The information needed to make the procedure manual is provided by each one of the people in charge of the correspondent departments, gathered through interviews and questionnaires. The development of this document allows to clarify the activities developed by the institution, and works as a tool to speed up the processes created in the manual.
Proyecto de Graduación (Bachillerato en Administración de Empresas) Instituto Tecnológico de Costa Rica. Escuela de Administración de Empresas, 2014.
Keywords: Manual de procedimientos; Recursos Humanos